A 980nm semiconductor laser with optimized corrosion stop layer and its preparation method
By optimizing the growth conditions and structural design of the corrosion end layer in the 980nm semiconductor laser, the defect problem caused by AS/P switching is solved, and the optimization efficiency is optimized through the ALGAAS limit layer of the high -algaas, and higher -quality materials have been achieved, and higher -quality materials are achieved. Growth and more efficient photoelectric conversion.
Patent Information
- Application Number
- CN202110461647.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-04-27
AI Technical Summary
The existing 980nm semiconductor lasers have defects caused by As/P switching during material growth, resulting in poor material growth quality, and the growth interface between the GaInP corrosion termination layer and the AlGaAs restriction layer is lacking optimization, affecting the photoelectric conversion efficiency.
By optimizing the growth conditions and structural design of the corrosion end layer, the GAASP transition layer is adopted to optimize the growth interface of the GainP corrosion end layer and the AlgaAS limit layer, and use the Algaas of the high Algaa as the second upper limit layer to reduce the light field to the cap hat cap Light absorption caused by layer offset.
Reduce the deficiency density introduced by AS/P switching, improve the quality of material growth, and improve the photoelectric conversion efficiency through pressure strain compensation and optimization of light field offset optimization.
Smart Images

Figure CN115249946B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a 980nm semiconductor laser with an optimized corrosion stop layer and a preparation method thereof, belonging to the technical field of semiconductor lasers. Background Art
[0002] 980nm semiconductor laser is the pumping light source of many new solid laser materials. It can obtain lasers in the two wavelength ranges of 1.55-1.66μm and 2.60-2.90μm, and is the most ideal pumping source for erbium doped fiber amplifier (EDFA). In order to improve the coupling efficiency between semiconductor laser and single-mode fiber, single-mode output is usually required, and the ridge waveguide depth is the key parameter for optimizing the performance of ridge waveguide devices.
[0003] Chinese patent document CN111404025A discloses an epitaxial growth method of AlGaAs / AlGaInP mixed material, which pauses the growth during the growth of AlGaAs material, stops the V group source to achieve growth pause, depletes As atoms in the reaction chamber, and grows AlGaInP material on the surface of the AlGaAs material after the growth pause, thereby reducing defects and dislocations at the interface of the mixed material. However, this growth method is difficult to completely remove AsH3 in the reaction chamber, resulting in material mixing at the growth interface; secondly, the surface of the AlGaAs material, as PH3 is thermally decomposed, As and P diffuse each other, resulting in reconstruction of the surface of the AlGaAs material, making it difficult to control defects and dislocations.
[0004] Chinese patent CN104242057A discloses a semiconductor laser with low operating voltage and high power conversion efficiency, using GaInAsP quaternary alloy as a bandgap transition layer, and reducing the band step at the interface of GaAs and AlGaInP, thereby reducing the operating voltage and improving the photoelectric conversion efficiency. However, this growth method has the following problems: first, the growth of GaInAsP quaternary alloy is difficult, and the composition control is uneven; second, there is no precedent for the application of GaInP corrosion stop layer and AlGaAs material. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a 980nm semiconductor laser with an optimized corrosion stop layer and a preparation method thereof. By optimizing the growth conditions and structural design of the corrosion stop layer, a GaAsP transition layer is adopted, and the growth interface between the GaInP corrosion stop layer and the AlGaAs confinement layer is optimized, the defect density of As / P conversion is reduced, and the material growth quality is improved; at the same time, a high Al component AlGaAs is used as a second upper confinement layer to reduce light absorption caused by the deviation of the light field to the cap layer, thereby improving the photoelectric conversion efficiency.
[0006] The technical solution of the present invention is as follows:
[0007] The first aspect of the present invention provides a 980nm semiconductor laser with an optimized corrosion stop layer, the laser comprising a substrate, a buffer layer, a lower confinement layer, a lower waveguide layer, an In x3 Ga 1-x3 As first quantum well, barrier layer, In x5 Ga 1-x5 As second quantum well, upper waveguide layer, first upper confinement layer, GaAs 1-x8 P x8 The first transition layer, Ga 1-x9 In x9 P etch stop layer, GaAs 1-x10 P x10 a second transition layer, a second upper limiting layer and a cap layer;
[0008] Among them, 0.05≤x3≤0.15, 0.05≤x5≤0.15, 0.7≤x8≤0.9, 0.5≤x9≤0.6, 0.7≤x10≤0.9.
[0009] Among them, the values of x3 and x5 realize the quantum well lasing wavelength of 980nm; GaAs 1-x8 P x8 The first transition layer and GaAs 1- x10 P x10 The second transition layer optimizes Ga 1-x9 In x9 The P corrosion stop layer and the growth interface of the restriction layer reduce the defects introduced by the As / P switching, which leads to the deterioration of the material growth quality. At the same time, the compressive strain GaInP and the tensile strain GaAsP strain compensation optimize the material growth quality;
[0010] Al x11 Ga 1-x11 The As second upper confinement layer adopts a high Al component to shift the light field toward the active area, reduce the absorption of the cap layer, and improve the photoelectric conversion efficiency.
[0011] Preferably, according to the present invention, the 980nm semiconductor laser with optimized corrosion stop layer includes one or more of the following conditions:
[0012] I. The substrate is a GaAs substrate;
[0013] II. The buffer layer is a GaAs buffer layer;
[0014] III. The lower limiting layer is Al x1 Ga 1-x1 As lower limiting layer; 0.3≤x1≤0.5;
[0015] IV. The lower waveguide layer is Al x2 Ga 1-x2 As lower waveguide layer; 0.05≤x2≤0.3;
[0016] V. The barrier layer is Al x4 Ga 1-x4 As barrier layer; 0.05≤x4≤0.3;
[0017] VI. The upper waveguide layer is Al x6 Ga 1-x6 As upper waveguide layer; 0.05≤x6≤0.3;
[0018] VII. The first upper confinement layer is Al x7 Ga 1-x7 As first upper limiting layer; 0.3≤x7≤0.5;
[0019] VIII. The second upper confinement layer is Al x11 Ga 1-x11 As second upper limiting layer; 0.4≤x11≤0.7;
[0020] IX. The cap layer is a GaAs cap layer.
[0021] According to the preferred embodiment of the present invention, in the 980nm semiconductor laser of the optimized corrosion stop layer, In x3 Ga 1-x3 The thickness of the As first quantum well is 4-7nm, unintentionally doped, 0.05≤x3≤0.15; In x5 Ga 1-x5 The thickness of the second quantum well of As is 4-7nm, unintentionally doped, 0.05≤x5≤0.15; GaAs 1-x8 P x8 The first transition layer is P-type GaAs 1-x8 P x8 The first transition layer has a thickness of 1-3 nm and a doping concentration of 5E17-1.5E18 atoms / cm 3 , 0.7≤x8≤0.9; Ga 1-x9 In x9 P corrosion stop layer is P-type Ga 1-x9 In x9 P corrosion stop layer, thickness is 5-20nm, doping concentration is 5E17-2E18 atoms / cm 3 , 0.5≤x9≤0.6; GaAs 1-x10 P x10 The second transition layer is P-type GaAs 1-x10 P x10 The second transition layer has a thickness of 1-3 nm and a doping concentration of 5E17-1.5E18 atoms / cm3 , 0.7≤x10≤0.9.
[0022] According to the present invention, the 980nm semiconductor laser with optimized corrosion stop layer includes one or more of the following conditions:
[0023] ①. The buffer layer is a GaAs buffer layer, and the doping concentration of the GaAs buffer layer is 2E18 to 5E18 atoms / cm 3 , thickness is 0.1~0.3μm;
[0024] ②. The lower limiting layer is N-type Al x1 Ga 1-x1 As lower confinement layer, N-type Al x1 Ga 1-x1 The thickness of the As lower confinement layer is 1.2-2 μm, and the doping concentration is 5E17-2E18 atoms / cm 3 , 0.3≤x1≤0.5;
[0025] ③. The lower waveguide layer is Al x2 Ga 1-x2 As lower waveguide layer, Al x2 Ga 1-x2 The thickness of the waveguide layer under As is 30-100 nm, not intentionally doped, 0.05≤x2≤0.3;
[0026] ④. The barrier layer is Al x4 Ga 1-x4 As barrier layer, Al x4 Ga 1-x4 The thickness of the As barrier layer is 4-7nm, unintentionally doped, 0.3≤x3≤0.5;
[0027] ⑤. The upper waveguide layer is Al x6 Ga 1-x6 As upper waveguide layer, Al x6 Ga 1-x6 The thickness of the waveguide layer on As is 30-100 nm, unintentionally doped, 0.05≤x6≤0.3;
[0028] ⑥. The first upper confinement layer is P-type Al x7 Ga 1-x7 As first upper confinement layer, P-type Al x7 Ga 1-x7 The thickness of the As first upper confinement layer is 0.1-0.3 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.3≤x7≤0.5;
[0029] ⑦. The second upper confinement layer is P-type Al x11 Ga 1-x11As second upper confinement layer, P-type Al x11 Ga 1-x11 The thickness of the second upper confinement layer of As is 0.5-1.2 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.4≤x11≤0.7;
[0030] ⑧. The cap layer is a GaAs cap layer with a thickness of 0.1-0.5 μm and a doping concentration of 4E19-1E20 atoms / cm 3 .
[0031] According to the present invention, the 980nm semiconductor laser with optimized corrosion stop layer includes one or more of the following conditions:
[0032] ①. The buffer layer is a GaAs buffer layer, and the doping concentration of the GaAs buffer layer is 4E18 atoms / cm 3 , thickness is 0.2μm;
[0033] ②. The lower limiting layer is N-type Al x1 Ga 1-x1 As lower confinement layer, N-type Al x1 Ga 1-x1 The thickness of the As lower confinement layer is 1.8 μm and the doping concentration is 1E18 atoms / cm 3 , x1=0.35;
[0034] ③. The lower waveguide layer is Al x2 Ga 1-x2 As lower waveguide layer, Al x2 Ga 1-x2 The thickness of the waveguide layer under As is 40 nm, it is not intentionally doped, and x2 = 0.1;
[0035] ④. The barrier layer is Al x4 Ga 1-x4 As barrier layer, Al x4 Ga 1-x4 The thickness of the As barrier layer is 5 nm, not intentionally doped, x4 = 0.35;
[0036] ⑤. The upper waveguide layer is Al x6 Ga 1-x6 As upper waveguide layer, Al x6 Ga 1-x6 The thickness of the waveguide layer on As is 40 nm, it is not intentionally doped, and x6 = 0.1;
[0037] ⑥. The first upper confinement layer is P-type Al x7 Ga 1-x7 As first upper confinement layer, P-type Al x7 Ga 1-x7The thickness of the As first upper confinement layer is 0.15 μm and the doping concentration is 7E17 atoms / cm 3 , x7=0.35;
[0038] ⑦. The second upper confinement layer is P-type Al x11 Ga 1-x11 As second upper confinement layer, P-type Al x11 Ga 1-x11 The thickness of the second upper confinement layer of As is 0.8 μm and the doping concentration is 1E18 atoms / cm 3 , x11=0.5;
[0039] ⑧. The cap layer is GaAs cap layer with a thickness of 0.2 μm and a doping concentration of 7E19 atoms / cm 3 .
[0040] The second aspect of the present invention provides a method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer, the method comprising the following steps: performing surface heat treatment on a substrate in an MOCVD growth chamber, and then epitaxially growing a buffer layer, a lower transition layer, a lower confinement layer, a lower waveguide layer, an In layer from bottom to top. x3 Ga 1-x3 As first quantum well, barrier layer, In x5 Ga 1- x5 As second quantum well, upper waveguide layer, first upper confinement layer, GaAs 1-x8 P x8 The first transition layer, Ga 1-x9 In x9 P etch stop layer, GaAs 1-x10 P x10 a second transition layer, a second upper limiting layer and a cap layer;
[0041] Among them, x3 Ga 1-x3 As first quantum well and In x5 Ga 1-x5 The conditions of the second quantum well of As are: growth temperature 640-660℃, introduction of TMIn, TMGa and AsH3; 1-x8 P x8 First transition layer and GaAs 1-x10 P x10 The conditions for the second transition layer are: growth temperature 690-710℃, introduction of TMGa, AsH3 and PH3; 1-x9 In x9 The conditions of the P corrosion stop layer are: growth temperature 690-710℃, introduction of TMIn, TMGa and PH3.
[0042] Specifically, a method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer comprises the following steps:
[0043] S1, placing the GaAs substrate in the growth chamber of the MOCVD equipment, heating the H2 environment to 720±10°C for baking, and introducing AsH3 to perform surface heat treatment on the GaAs substrate;
[0044] S2, slowly lowering the temperature to 680±10°C at a rate of no more than 60°C / min, continuing to introduce TMGa and AsH3 to grow a GaAs buffer layer on the GaAs substrate;
[0045] S3, the temperature is maintained at 680±10°C, TMAl, TMGa and AsH3 are introduced, and N-type Al is grown on the buffer layer. x1 Ga 1-x1 As lower limiting layer;
[0046] S4, the temperature is slowly changed to 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the lower confinement layer. x2 Ga 1-x2 As lower waveguide layer;
[0047] S5, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the lower waveguide layer. x3 Ga 1-x3 As first quantum well;
[0048] S6, the temperature is maintained at 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the first quantum well. x4 Ga 1-x4 As barrier layer;
[0049] S7, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the barrier layer. x5 Ga 1-x5 As second quantum well;
[0050] S8, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the second quantum well. x6 Ga 1-x6 As upper waveguide layer;
[0051] S9, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the upper waveguide layer. x7 Ga 1-x7 As first upper limiting layer;
[0052] S10, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the first upper confinement layer. 1-x8 P x8 First transition layer;
[0053] S11, the temperature is maintained at 680±10°C, TMIn, TMGa and PH3 are introduced, and P-type Ga is grown on the first transition layer. 1-x9 In x9 P corrosion stop layer;
[0054] S12, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the etching stop layer 1-x10 P x10 Second transition layer;
[0055] S13, the temperature is slowly raised to 700±10°C, the heating rate is not less than 45°C / min, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the second transition layer. x11 Ga 1-x11 As the second upper limiting layer;
[0056] S14, lowering the temperature to 540±10°C, continuing to introduce TMGa and AsH3, and growing a GaAs cap layer on the upper confinement layer.
[0057] According to a preferred embodiment of the present invention, in step S2, the doping concentration of the GaAs buffer layer is 2E18 to 5E18 atoms / cm 3 , with a thickness of 0.1 to 0.3 μm; further preferably, the thickness of the GaAs transition layer is 0.2 μm, and the doping concentration is 4E18 atoms / cm 3 .
[0058] According to the preferred embodiment of the present invention, in step S3, the N-type Al x1 Ga 1-x1 The thickness of the As lower confinement layer is 1.2-2 μm, and the doping concentration is 5E17-2E18 atoms / cm 3 , 0.3≤x1≤0.5; further preferably, x1=0.35, the thickness is 1.8μm, and the doping concentration is 1E18 atoms / cm 3 .
[0059] According to the preferred embodiment of the present invention, in step S4, the Al x2 Ga 1-x2 The thickness of the waveguide layer under As is 30-100 nm, is not intentionally doped, 0.05≤x2≤0.3; further preferably, x2=0.1, and the thickness is 40 nm.
[0060] According to the preferred embodiment of the present invention, in step S5, the In x3 Ga 1-x3 The thickness of the As first quantum well is 4-7 nm, it is not intentionally doped, 0.05≤x3≤0.15; further preferably, x3=0.1, and the thickness is 5 nm.
[0061] According to the preferred embodiment of the present invention, in step S6, Al x4 Ga 1-x4 The thickness of the As barrier layer is 4-7 nm, it is not intentionally doped, 0.3≤x3≤0.5; more preferably, x4=0.35, and the thickness is 5 nm.
[0062] According to a preferred embodiment of the present invention, in step S7, the In x5 Ga 1-x5 The thickness of the As second quantum well is 4-7 nm, it is not intentionally doped, 0.05≤x5≤0.15; further preferably, x5=0.1, and the thickness is 5 nm.
[0063] According to the preferred embodiment of the present invention, in step S8, the Al x6 Ga 1-x6 The thickness of the upper waveguide layer of As is 30-100nm, unintentionally doped, 0.05≤x6≤0.3; further preferably, x6=0.1, and the thickness is 40nm. The thickness of the upper and lower waveguide layers is relatively thin, in order to allow the light field to enter the confinement layer, expand the light spot, increase the cavity surface damage threshold, increase the absorption loss of the high-order mode, and increase the maximum output power of the fundamental mode.
[0064] According to the preferred embodiment of the present invention, in step S9, the P-type Al x7 Ga 1-x7 The thickness of the As first upper confinement layer is 0.1-0.3 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.3≤x7≤0.5; further preferably, x7=0.35, the thickness is 0.15μm, and the doping concentration is 7E17 atoms / cm 3 .
[0065] According to the preferred embodiment of the present invention, in step S10, the P-type GaAs 1-x8 P x8 The thickness of the first transition layer is 1-3 nm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.7≤x8≤0.9; further preferably, x8=0.85, the thickness is 2nm, and the doping concentration is 7E17 atoms / cm 3 .GaAs 1-x8 P x8The first transition layer has a lattice constant smaller than that of the GaAs substrate and is subjected to tensile strain.
[0066] According to the preferred embodiment of the present invention, in step S11, the P-type Ga 1-x9 In x9 The thickness of the P corrosion stop layer is 5-20nm, and the doping concentration is 5E17-2E18 atoms / cm 3 , 0.5≤x9≤0.6; further preferably, x9=0.55, the thickness is 10nm, and the doping concentration is 1E18 atoms / cm 3 . 1-x9 In x9 The lattice constant of the P corrosion stop layer is greater than that of the GaAs substrate and is subject to compressive strain.
[0067] According to the preferred embodiment of the present invention, in step S12, the P-type GaAs 1-x10 P x10 The thickness of the second transition layer is 1-3 nm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.7≤x10≤0.9; further preferably, x10=0.85, the thickness is 2nm, and the doping concentration is 7E17 atoms / cm 3 .GaAs 1-x10 P x10 The first transition layer has a lattice constant smaller than that of the GaAs substrate and is subjected to tensile strain.
[0068] According to the preferred embodiment of the present invention, in step S13, the P-type Al x11 Ga 1-x11 The thickness of the second upper confinement layer of As is 0.5-1.2 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.4≤x11≤0.7; further preferably, x11=0.5, the thickness is 0.8μm, and the doping concentration is 1E18 atoms / cm 3 The Al component of the second upper confinement layer is higher than that of the first upper confinement layer, so that the light field is shifted toward the active area, the light absorption loss of the GaAs cap layer is reduced, and the photoelectric conversion efficiency is improved.
[0069] According to a preferred embodiment of the present invention, in step S14, the cap layer has a thickness of 0.1-0.5 μm and a doping concentration of 4E19-1E20 atoms / cm 3 ; Further preferably, the thickness is 0.2 μm and the doping concentration is 7E19 atoms / cm 3 .
[0070] The beneficial effects of the present invention are:
[0071] The present invention uses GaAs 1-x8 P x8The first transition layer and GaAs 1-x10 P x10 The second transition layer optimizes the interface between the GaInP corrosion stop layer and the AlGaAs confinement layer, reduces the defects introduced by the As / P switching, and causes the material growth quality to deteriorate. At the same time, the compressive strain GaInP and the tensile strain GaAsP strain compensation optimizes the material growth quality. x11 Ga 1-x11 The As second upper confinement layer uses a high Al component to shift the light field toward the active area, reduce the absorption of the cap layer, and improve the photoelectric conversion efficiency of the laser. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 Schematic diagram of the structure of a conventional laser device (a) and the laser of the present invention (b);
[0073] 1 is GaAs substrate, 2 is GaAs buffer layer, 3 is Al x1 Ga 1-x1 As lower limiting layer, 4 is Al x2 Ga 1-x2 As lower waveguide layer, 5 is In x3 Ga 1-x3 As is the first quantum well, 6 is Al x4 Ga 1-x4 As barrier layer, 7 is In x5 Ga 1-x5 As is the second quantum well, 8 is Al x6 Ga 1-x6 As upper waveguide layer, 9 is Al x7 Ga 1-x7 As is the first upper confinement layer, 10 is GaAs 1-x8 P x8 The first transition layer, 11 is Ga 1-x9 In x9 P etching stop layer, 12 is GaAs 1-x10 P x10 The second transition layer, 13 is Al x11 Ga 1-x11 The second upper confinement layer 14 is a GaAs cap layer.
[0074] Figure 2 These are test result diagrams of TEM test (upper) and EDS test (lower) of the upper and lower surfaces of the laser GaInP corrosion stop layer described in the present invention.
[0075] In the figure, the starting position of the arrow is the second upper confinement layer, Figure (a) is a TEM image, and Figure (b) is an EDS image. The ordinate is the atomic percentage content, and the abscissa is the test depth. DETAILED DESCRIPTION
[0076] The present invention will be further described below with reference to the embodiments and drawings, but is not limited thereto.
[0077] Embodiment 1:
[0078] A 980nm semiconductor laser with an optimized corrosion stop layer, the laser comprising a GaAs substrate, a GaAs buffer layer, an Al x1 Ga 1-x1 As lower limiting layer, Al x2 Ga 1-x2 As lower waveguide layer, In x3 Ga 1-x3 As first quantum well, Al x4 Ga 1-x4 As barrier layer, In x5 Ga 1-x5 As second quantum well, Al x6 Ga 1-x6 As upper waveguide layer, Al x7 Ga 1-x7 As first upper confinement layer, GaAs 1-x8 P x8 The first transition layer, Ga 1-x9 In x9 P etch stop layer, GaAs 1-x10 P x10 The second transition layer, Al x11 Ga 1-x11 As second upper confinement layer and GaAs cap layer,
[0079] The preparation method comprises the following steps:
[0080] S1, placing the GaAs substrate in the growth chamber of the MOCVD equipment, heating the H2 environment to 720±10°C for baking, and introducing AsH3 to perform surface heat treatment on the GaAs substrate;
[0081] S2, slowly lower the temperature to 680±10℃, with the cooling rate no greater than 60℃ / min, continue to introduce TMGa and AsH3, and grow a GaAs buffer layer on the GaAs substrate; the growth thickness is 0.2μm, and the doping concentration is 4E18 atoms / cm 3 ;
[0082] S3, the temperature is maintained at 680±10°C, TMAl, TMGa and AsH3 are introduced, and N-type Al is grown on the buffer layer. x1 Ga 1-x1 As lower confinement layer; growth thickness is 1.8 μm, x1=0.35, doping concentration is 1E18 atoms / cm 3 ;
[0083] S4, the temperature is slowly changed to 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the lower confinement layer. x2 Ga 1-x2 As lower waveguide layer; growth thickness is 40nm, x2=0.1, unintentional doping;
[0084] S5, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the lower waveguide layer. x3 Ga 1-x3 As first quantum well; growth thickness is 5nm, x3=0.1, unintentional doping;
[0085] S6, the temperature is maintained at 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the first quantum well. x4 Ga 1-x4 As barrier layer; growth thickness is 5nm, x4=0.35, unintentional doping;
[0086] S7, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the barrier layer. x5 Ga 1-x5 As second quantum well; growth thickness is 5nm, x5=0.1, unintentional doping;
[0087] S8, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the second quantum well. x6 Ga 1-x6 As upper waveguide layer; growth thickness 40nm, x6 = 0.1, unintentional doping;
[0088] S9, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the upper waveguide layer. x7 Ga 1-x7 As first upper confinement layer; growth thickness is 0.15 μm, x7=0.35, doping concentration is 7E17 atoms / cm 3 ;
[0089] S10, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the first upper confinement layer. 1-x8 P x8 First transition layer; growth thickness is 2nm, x8=0.85, doping concentration is 7E17 atoms / cm 3 ;
[0090] S11, the temperature is maintained at 680±10°C, TMIn, TMGa and PH3 are introduced, and P-type Ga is grown on the first transition layer. 1-x9 In x9 P corrosion stop layer; growth thickness is 10nm, x9=0.55, doping concentration is 1E18 atoms / cm 3 ;
[0091] S12, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the etching stop layer 1-x10 P x10 Second transition layer;
[0092] The growth thickness is 2nm, x10=0.85, and the doping concentration is 7E17 atoms / cm 3 ;
[0093] S13, the temperature is slowly raised to 700±10°C, the heating rate is not less than 45°C / min, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the second transition layer. x11 Ga 1-x11 As second upper confinement layer; growth thickness is 0.8 μm, x11=0.5, doping concentration is 1E18 atoms / cm 3 ;
[0094] S14, lowering the temperature to 540±10°C, continuing to introduce TMGa and AsH3, growing a GaAs cap layer on the second upper confinement layer, with a growth thickness of 0.2 μm and a doping concentration of 7E19 atoms / cm 3 .
[0095] Conventional laser devices such as Figure 1 As shown in (a), the structure of the laser described in this embodiment 1 is as follows Figure 1 (b) is shown. Figure 1 (a) and Figure 1 (b) By comparison, it can be seen that in this embodiment, GaAs 1-x10 P x10 The second transition layer optimizes the growth interface between the GaInP corrosion stop layer and the AlGaAs confinement layer, reduces the defect density introduced by As / P switching, and improves the interface growth quality; and the strain compensation of the tensile strained GaInP corrosion stop layer can improve the material growth quality, and improve the photoelectric conversion efficiency and reliability.
[0096] Embodiment 2:
[0097] A method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer, comprising the following steps:
[0098] S1, placing the GaAs substrate in the growth chamber of the MOCVD equipment, heating the H2 environment to 720±10°C for baking, and introducing AsH3 to perform surface heat treatment on the GaAs substrate;
[0099] S2, slowly lower the temperature to 680±10℃, with the cooling rate no greater than 60℃ / min, continue to introduce TMGa and AsH3, and grow a GaAs buffer layer on the GaAs substrate; the growth thickness is 0.2μm, and the doping concentration is 4E18 atoms / cm 3 ;
[0100] S3, the temperature is maintained at 680±10°C, TMAl, TMGa and AsH3 are introduced, and N-type Al is grown on the buffer layer. x1 Ga 1-x1 As lower confinement layer; growth thickness is 1.5 μm, x1=0.4, doping concentration is 7E17 atoms / cm 3 ;
[0101] S4, the temperature is slowly changed to 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the lower confinement layer. x2 Ga 1-x2 As lower waveguide layer; growth thickness is 60nm, x2=0.2, unintentional doping;
[0102] S5, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the lower waveguide layer. x3 Ga 1-x3 As first quantum well; growth thickness is 6nm, x3=0.15, unintentional doping;
[0103] S6, the temperature is maintained at 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the first quantum well. x4 Ga 1-x4 As barrier layer; growth thickness is 6nm, x4=0.4, unintentional doping;
[0104] S7, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the barrier layer. x5 Ga 1-x5 As second quantum well; growth thickness is 6nm, x5=0.15, unintentional doping;
[0105] S8, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the second quantum well. x6 Ga 1-x6 As upper waveguide layer; growth thickness 60nm, x6=0.2, unintentional doping;
[0106] S9, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the upper waveguide layer. x7 Ga 1-x7 As first upper confinement layer; growth thickness is 0.2 μm, x7=0.4, doping concentration is 9E17 atoms / cm 3 ;
[0107] S10, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the first upper confinement layer. 1-x8 P x8 The first transition layer has a growth thickness of 1 nm, x8 = 0.8, and a doping concentration of 9E17 atoms / cm 3 ;
[0108] S11, the temperature is maintained at 680±10°C, TMIn, TMGa and PH3 are introduced, and P-type Ga is grown on the first transition layer. 1-x9 In x9 P corrosion stop layer; growth thickness is 15nm, x9=0.5, doping concentration is 9E17 atoms / cm 3 ;
[0109] S12, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the etching stop layer 1-x10 P x10 Second transition layer; growth thickness is 1nm, x10=0.8, doping concentration is 9E17 atoms / cm 3 ;
[0110] S13, the temperature is slowly raised to 700±10°C, the heating rate is not less than 45°C / min, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the second transition layer. x11 Ga 1-x11 As second upper confinement layer; growth thickness is 0.8 μm, x11=0.5, doping concentration is 1E18 atoms / cm 3 ;
[0111] S14, lower the temperature to 540±10°C, continue to introduce TMGa and AsH3, and grow a GaAs cap layer on the second upper confinement layer with a growth thickness of 0.2 μm and a doping concentration of 7E19 atoms / cm 3 .
[0112] Embodiment 3:
[0113] A method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer, wherein the steps are as described in Example 2, except that in S10, x8=0.9, and the thickness is 3nm; in S11, x9=0.6, and the thickness is 18nm; in S12, x10=0.9, and the thickness is 3nm.
[0114] Test example
[0115] The upper and lower positions of the corrosion stop layer of the laser described in Example 1 of the present invention are observed using a transmission electron microscope (TEM), and the upper and lower positions of the corrosion stop layer are analyzed using an energy dispersive spectrometer (EDS).
[0116] TEM, or transmission electron microscopy, projects an accelerated and focused electron beam onto a very thin sample. The electrons collide with atoms in the sample and change direction, resulting in three-dimensional angular scattering. The size of the scattering angle is related to the density and thickness of the sample, so different images of light and dark can be formed, thereby observing structures smaller than 0.2μm that cannot be seen clearly under an optical microscope.
[0117] EDS is an energy dispersive spectrometer, which is usually used in conjunction with a scanning electron microscope and a transmission electron microscope. When X-ray photons enter the detector, the characteristic X-rays of different elements have different frequencies. By detecting the energy of the photons, the elements can be determined for qualitative analysis. Quantitative analysis can be achieved by theoretical calculations using the intensity of the X-rays.
[0118] From the TEM test image, we can see that Ga 1-x9 In x9 The interface between the P corrosion stop layer and the limiting layer is clear, and no large number of dislocations are generated; the EDS test image shows that Ga 1-x9 In x9 There is an obvious change in elemental composition between the P corrosion stop layer and the limiting layer; however, due to the thin GaAsP layer, EDS cannot completely distinguish them. 1-x10 P x10 The second transition layer reduces defects introduced by As / P switching and improves the interface growth quality.
Claims
1. A 980nm semiconductor laser with an optimized corrosion stop layer, the laser comprising a substrate, a buffer layer, a lower confinement layer, a lower waveguide layer, an In x3 Ga 1-x3 As first quantum well, barrier layer, In x5 Ga 1-x5 As second quantum well, upper waveguide layer, first upper confinement layer, GaAs 1-x8 P x8 The first transition layer, Ga 1-x9 In x9 P etch stop layer, GaAs 1-x10 P x10 a second transition layer, a second upper limiting layer and a cap layer; in, 0.05≤x3≤0.15, 0.05≤x5≤0.15, 0.7≤x8≤0.9, 0.5≤x9≤0.6, 0.7≤x10≤0.
9.
2. The 980nm semiconductor laser with optimized corrosion stop layer according to claim 1, characterized in that: The 980nm semiconductor laser with optimized corrosion stop layer includes one or more of the following conditions: I. The substrate is a GaAs substrate; II. The buffer layer is a GaAs buffer layer; III. The lower limiting layer is Al x1 Ga 1-x1 As lower limiting layer; 0.3≤x1≤0.5; IV. The lower waveguide layer is Al x2 Ga 1-x2 As lower waveguide layer; 0.05≤x2≤0.3; V. The barrier layer is Al x4 Ga 1-x4 As barrier layer; 0.05≤x4≤0.3; VI. The upper waveguide layer is Al x6 Ga 1-x6 As upper waveguide layer; 0.05≤x6≤0.3; VII. The first upper confinement layer is Al x7 Ga 1-x7 As first upper limiting layer; 0.3≤x7≤0.5; VIII. The second upper confinement layer is Al x11 Ga 1-x11 As second upper limiting layer; 0.4≤x11≤0.7; IX. The cap layer is a GaAs cap layer.
3. The 980nm semiconductor laser with optimized corrosion stop layer according to claim 1, characterized in that: In the 980nm semiconductor laser with optimized corrosion stop layer, In x3 Ga 1-x3 The thickness of the As first quantum well is 4-7nm, unintentionally doped, 0.05≤x3≤0.15; In x5 Ga 1-x5 The thickness of the second quantum well of As is 4-7nm, unintentionally doped, 0.05≤x5≤0.15; GaAs 1-x8 P x8 The first transition layer is P-type GaAs 1-x8 P x8 The first transition layer has a thickness of 1-3 nm and a doping concentration of 5E17-1.5E18 atoms / cm 3 , 0.7≤x8≤0.9; Ga 1-x9 In x9 P corrosion stop layer is P-type Ga 1-x9 In x9 P corrosion stop layer, thickness is 5-20nm, doping concentration is 5E17-2E18 atoms / cm 3 , 0.5≤x9≤0.6; GaAs 1-x10 P x10 The second transition layer is P-type GaAs 1-x10 P x10 The second transition layer has a thickness of 1-3 nm and a doping concentration of 5E17-1.5E18 atoms / cm 3 , 0.7≤x10≤0.
9.
4. The 980nm semiconductor laser with optimized corrosion stop layer according to claim 1, characterized in that: The 980nm semiconductor laser with optimized corrosion stop layer includes one or more of the following conditions: ①. The buffer layer is a GaAs buffer layer, and the doping concentration of the GaAs buffer layer is 2E18-5E18 atoms / cm 3 , thickness is 0.1-0.3μm; ②. The lower limiting layer is N-type Al x1 Ga 1-x1 As lower confinement layer, N-type Al x1 Ga 1-x1 The thickness of the As lower confinement layer is 1.2-2 μm, and the doping concentration is 5E17-2E18 atoms / cm 3 , 0.3≤x1≤0.5; ③. The lower waveguide layer is Al x2 Ga 1-x2 As lower waveguide layer, Al x2 Ga 1-x2 The thickness of the waveguide layer under As is 30-100 nm, not intentionally doped, 0.05≤x2≤0.3; ④. The barrier layer is Al x4 Ga 1-x4 As barrier layer, Al x4 Ga 1-x4 The thickness of the As barrier layer is 4-7nm, unintentionally doped, 0.3≤x3≤0.5; ⑤. The upper waveguide layer is Al x6 Ga 1-x6 As upper waveguide layer, Al x6 Ga 1-x6 The thickness of the waveguide layer on As is 30-100 nm, not intentionally doped, 0.05≤x6≤0.3; ⑥. The first upper confinement layer is P-type Al x7 Ga 1-x7 As first upper confinement layer, P-type Al x7 Ga 1-x7 The thickness of the As first upper confinement layer is 0.1-0.3 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.3≤x7≤0.5; ⑦. The second upper confinement layer is P-type Al x11 Ga 1-x11 As second upper confinement layer, P-type Al x11 Ga 1-x11 The thickness of the second upper confinement layer of As is 0.5-1.2 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.4≤x11≤0.7; ⑧. The cap layer is a GaAs cap layer with a thickness of 0.1-0.5 μm and a doping concentration of 4E19-1E20 atoms / cm 3 .
5. The 980nm semiconductor laser with optimized corrosion stop layer according to claim 1, characterized in that: The 980nm semiconductor laser with optimized corrosion stop layer includes one or more of the following conditions: ①. The buffer layer is a GaAs buffer layer, and the doping concentration of the GaAs buffer layer is 4E18 atoms / cm 3 , thickness is 0.2μm; ②. The lower limiting layer is N-type Al x1 Ga 1-x1 As lower confinement layer, N-type Al x1 Ga 1-x1 The thickness of the As lower confinement layer is 1.8 μm and the doping concentration is 1E18 atoms / cm 3 , x1=0.35; ③. The lower waveguide layer is Al x2 Ga 1-x2 As lower waveguide layer, Al x2 Ga 1-x2 The thickness of the waveguide layer under As is 40 nm, it is not intentionally doped, and x2 = 0.1; ④. The barrier layer is Al x4 Ga 1-x4 As barrier layer, Al x4 Ga 1-x4 The thickness of the As barrier layer is 5 nm, not intentionally doped, x4 = 0.35; ⑤. The upper waveguide layer is Al x6 Ga 1-x6 As upper waveguide layer, Al x6 Ga 1-x6 The thickness of the waveguide layer on As is 40 nm, it is not intentionally doped, and x6 = 0.1; ⑥. The first upper confinement layer is P-type Al x7 Ga 1-x7 As first upper confinement layer, P-type Al x7 Ga 1-x7 The thickness of the As first upper confinement layer is 0.15 μm and the doping concentration is 7E17 atoms / cm 3 , x7=0.35; ⑦. The second upper confinement layer is P-type Al x11 Ga 1-x11 As second upper confinement layer, P-type Al x11 Ga 1-x11 The thickness of the second upper confinement layer of As is 0.8 μm and the doping concentration is 1E18 atoms / cm 3 , x11=0.5; ⑧. The cap layer is GaAs cap layer with a thickness of 0.2 μm and a doping concentration of 7E19 atoms / cm 3 .
6. A method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer, characterized in that: The method comprises the following steps: performing surface heat treatment on the substrate in an MOCVD growth chamber, and then epitaxially growing a buffer layer, a lower transition layer, a lower restriction layer, a lower waveguide layer, an In layer from bottom to top. x3 Ga 1-x3 As first quantum well, barrier layer, In x5 Ga 1-x5 As second quantum well, upper waveguide layer, first upper confinement layer, GaAs 1-x8 P x8 The first transition layer, Ga 1-x9 In x9 P etch stop layer, GaAs 1-x10 P x10 a second transition layer, a second upper limiting layer and a cap layer; Among them, x3 Ga 1-x3 As first quantum well and In x5 Ga 1-x5 The conditions of the second quantum well of As are: growth temperature 640-660℃, introduction of TMIn, TMGa and AsH3; 1-x8 P x8 First transition layer and GaAs 1-x10 P x10 The conditions for the second transition layer are: growth temperature 690-710℃, introduction of TMGa, AsH3 and PH3; 1-x9 In x9 The conditions of the P corrosion stop layer are: growth temperature 690-710℃, introduction of TMIn, TMGa and PH3.
7. A method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer, characterized in that: The method comprises the following steps: S1, placing the GaAs substrate in the growth chamber of the MOCVD equipment, heating the H2 environment to 720±10°C for baking, and introducing AsH3 to perform surface heat treatment on the GaAs substrate; S2, slowly lowering the temperature to 680±10°C, with a cooling rate of no more than 60°C / min, and continuing to introduce TMGa and AsH3 to grow a GaAs buffer layer on the GaAs substrate; S3, the temperature is maintained at 680±10°C, TMAl, TMGa and AsH3 are introduced, and N-type Al is grown on the buffer layer. x1 Ga 1-x1 As lower limiting layer; S4, the temperature is slowly changed to 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the lower confinement layer. x2 Ga 1-x2 As lower waveguide layer; S5, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the lower waveguide layer. x3 Ga 1-x3 As first quantum well; S6, the temperature is maintained at 650±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the first quantum well. x4 Ga 1- x4 As barrier layer; S7, the temperature is maintained at 650±10°C, TMIn, TMGa and AsH3 are introduced, and In is grown on the barrier layer. x5 Ga 1-x5 As second quantum well; S8, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and Al is grown on the second quantum well. x6 Ga 1- x6 As upper waveguide layer; S9, the temperature is slowly changed to 680±10°C, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the upper waveguide layer. x7 Ga 1- x7 As first upper limiting layer; S10, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the first upper confinement layer. 1-x8 P x8 First transition layer; S11, the temperature is maintained at 680±10°C, TMIn, TMGa and PH3 are introduced, and P-type Ga is grown on the first transition layer. 1- x9 In x9 P corrosion stop layer; S12, the temperature is maintained at 680±10°C, TMGa, AsH3 and PH3 are introduced, and P-type GaAs is grown on the etching stop layer 1-x10 P x10 Second transition layer; S13, the temperature is slowly raised to 700±10°C, the heating rate is not less than 45°C / min, TMAl, TMGa and AsH3 are introduced, and P-type Al is grown on the second transition layer. x11 Ga 1-x11 As the second upper limiting layer; S14, lowering the temperature to 540±10°C, continuing to introduce TMGa and AsH3, and growing a GaAs cap layer on the upper confinement layer.
8. The method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer according to claim 7, characterized in that: In step S2, the doping concentration of the GaAs buffer layer is 2E18-5E18 atoms / cm 3 , thickness is 0.1-0.3μm; In step S3, the N-type Al x1 Ga 1-x1 The thickness of the As lower confinement layer is 1.2-2 μm, and the doping concentration is 5E17-2E18 atoms / cm 3 , 0.3≤x1≤0.5; In step S4, the Al x2 Ga 1-x2 The thickness of the waveguide layer under As is 30-100 nm, is not intentionally doped, and is 0.05≤x2≤0.
3.
9. The method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer according to claim 8, characterized in that: In step S2, the thickness of the GaAs transition layer is 0.2 μm and the doping concentration is 4E18 atoms / cm 3 ; In step S3, x1=0.35, thickness is 1.8 μm, and doping concentration is 1E18 atoms / cm 3 ; In step S4, x2=0.1, and the thickness is 40 nm.
10. The method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer according to claim 7, characterized in that: In step S5, the In x3 Ga 1-x3 The thickness of the As first quantum well is 4-7nm, unintentionally doped, 0.05≤x3≤0.15; In step S6, A1 x4 Ga 1-x4 The thickness of the As barrier layer is 4-7nm, unintentionally doped, 0.3≤x3≤0.5; In step S7, the In x5 Ga 1-x5 The thickness of the As second quantum well is 4-7nm, unintentionally doped, 0.05≤x5≤0.15; In step S8, the Al x6 Ga 1-x6 The thickness of the waveguide layer on As is 30-100 nm, not intentionally doped, 0.05≤x6≤0.3; In step S9, the P-type Al x7 Ga 1-x7 The thickness of the As first upper confinement layer is 0.1-0.3 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.3≤x7≤0.
5.
11. The method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer according to claim 10, characterized in that: In step S5, x3=0.1, thickness is 5 nm; In step S6, x4=0.35, thickness is 5 nm; In step S7, x5=0.1, thickness is 5 nm; In step S8, x6=0.1, thickness is 40 nm; In step S9, x7=0.35, thickness is 0.15 μm, and doping concentration is 7E17 atoms / cm 3 .
12. The method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer according to claim 7, characterized in that: In step S10, the P-type GaAs 1-x8 P x8 The thickness of the first transition layer is 1-3 nm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.7≤x8≤0.9; In step S11, the P-type Ga 1-x9 In x9 The thickness of the P corrosion stop layer is 5-20nm, and the doping concentration is 5E17-2E18 atoms / cm 3 , 0.5≤x9≤0.6; In step S12, the P-type GaAs 1-x10 P x10 The thickness of the second transition layer is 1-3 nm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.7≤x10≤0.9; In step S13, the P-type Al x11 Ga 1-x11 The thickness of the second upper confinement layer of As is 0.5-1.2 μm, and the doping concentration is 5E17-1.5E18 atoms / cm 3 , 0.4≤x11≤0.7; In step S14, the cap layer has a thickness of 0.1-0.5 μm and a doping concentration of 4E19-1E20 atoms / cm 3 .
13. The method for preparing a 980nm semiconductor laser with an optimized corrosion stop layer according to claim 12, characterized in that: In step S10, x8=0.85, thickness is 2nm, and doping concentration is 7E17 atoms / cm 3 ; In step S11, x9=0.55, thickness is 10nm, and doping concentration is 1E18 atoms / cm 3 ; In step S12, x10=0.85, thickness is 2nm, and doping concentration is 7E17 atoms / cm 3 ; In step S13, x11=0.5, the thickness is 0.8 μm, and the doping concentration is 1E18 atoms / cm 3 ; In step S14, the thickness is 0.2 μm and the doping concentration is 7E19 atoms / cm 3 .
Citation Information
Patent Citations
Semiconductor laser with low working voltage and high power conversion efficiency
CN104242057A
Epitaxial growth method of AlGaAs / AlGaInP mixed material
CN111404025A
HEMT device epitaxial structure and growth method thereof
CN111354791A
Low-power laser based on gradient waveguide layer and preparation method thereof
CN112398002A